Densities and excess molar volumes of methanol with three fatty acid methyl esters from 283.15 to 318.15 K. (October 2018) - Sun, Yanjun; Di, Gaolei; Xia, Juan; Wang, Xiaopo; Yang, Xiaohu; He, Siyuan
Abstract: The main components of biodiesel are fatty acid methyl esters (FAMEs) or fatty acid ethyl esters (FAEE). Methanol is commonly used as a reference molecule for modeling diesel fuel thermodynamics properties. In this work, experimental density data of the binary mixtures of methanol with three fatty acid methyl esters (methyl caprate, methyl laurate, methyl myristate) were reported at atmospheric pressure over the entire composition range at temperatures from 283.15 to 318.15 K. Density measurements were performed using an Anton Paar digital vibrating U-tube densimeter. Excess molar volumes were calculated from the experimental data and correlated as the Redlich-Kister equation for the binary mixtures. The optimized sets of parameters of the equation at each temperature were obtained by the least squares method.